Theory of Optimal Taxation and Current Tax Policy in Pakistan’s Agriculture (The Pakistan Development Review, 2001)
The theory of optimal taxation has tended to recast the existing literature of public finance into the mould of classical welfare economics by emphasising minimisation of dead weight losses resulting from the imposition of a tax or faulty tax structure. As such, these modern theories have much in common with the traditional approach in terms of efficiency and equity. In spite of this, however, the differences remain. For example, the former theories adhere strictly to the norms of classical welfare economics which treats individual consumers as utility maximisers where improvements in welfare involve change that makes one individual better-off without making someone else worse-off [Stern (1987)]. In contrast to the emphasis of traditional theories on lump-sum taxes, the optimum tax literature is concerned with the implication of using non-lump-sum taxes which have a wider range and therefore more useful to the policy-maker. The recent work on normative tax theory looks at the impact of taxation on individual decisions and the trade off between raising revenues or redistributing tax burdens and the efficiency losses [Atkinson (1987)]. Finally, the optimal tax literature may be more pragmatic in its approach than traditional works as it realistically deals with government objectives and constraints and combines them into models that are sufficiently rich to allow for differences between people regarding income and expenditure patterns.